TINJAUAN MOTIVASI PESERTA DIDIK PADA PEMBELAJARAN PJOK DI SMK NEGERI 4 KERINCI - Yogi Ariska; Asril; Afwa Raufi (EDU RESEARCH, 2023)
Learner motivation in participating in learning is very necessary. Motivation is a condition that causes or generates certain behaviours and gives direction and resilience to these behaviours. Based on observations that the author has made at SMK Negeri 4 Kerinci, PJOK learning activities have not been carried out properly according to the demands of the curriculum. This is indicated by the activity of students in participating in PJOK learning which lacks the attention and supervision of the PJOK teacher. The purpose of the study was to obtain information and an overview of the review of student motivation in PJOK Learning at SMK Negeri 4 Kerinci. This type of research is classified in the type of descriptive research that aims to describe and interpret the data as it is. The population in this study were all class X students of SMK N 4 Kerinci. Taking random sampling technique. After carrying out random sampling activities above, the selected sample in this study was class X OTKP, totalling 32 students. Based on the results of research on "Review of Student Motivation in Pjok Learning at SMK Negeri 4 Kerinci", it can be concluded: Review of Student Motivation in Pjok Learning at SMK Negeri 4 Kerinci is in the very good category with an achievement of 84.035% classified as very good. From the results of data analysis and description of the results of the review at SMK Negeri 4 Kerinci on indicators of the quality of facilities and infrastructure, classified as excellent with the acquisition of mean = 6.75 with an achievement of 96.43%. From the results of data analysis and description of the results of the review of facilities and infrastructure development on the indicators of facilities and infrastructure, classified as good with the acquisition of mean = 9.31 with 71.64% achievement.